2021
DOI: 10.1007/s12144-021-01369-4
|View full text |Cite
|
Sign up to set email alerts
|

Scanning the VIRUS: A study of dimensions of stress and coping with COVID-19

Abstract: The current research examines the psychosocial stressors that Indians are facing as a result of the COVID-19 pandemic, using a self-constructed COVID-19 Stress Scale (CSS). It also assesses the coping strategies being used currently. The sample comprised of 1009 Indians ranging between 17 and 83 years. The items of the CSS were constructed based on a review of existing scales, expert evaluations, and participant interviews. The factor structure of COVID-19 Stress Scale (CSS) was examined through the use of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…The gender affected the stress where females experienced higher stress than men. 7 Moreover, amid the pandemic, 'habit forming' behaviours like internet use and substance use have been reported to increase in adolescents and adults. 8 Owing to social restrictions laid out by the government to prevent the spread of infection, there has been a surge in internet use, both during and after the lockdown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gender affected the stress where females experienced higher stress than men. 7 Moreover, amid the pandemic, 'habit forming' behaviours like internet use and substance use have been reported to increase in adolescents and adults. 8 Owing to social restrictions laid out by the government to prevent the spread of infection, there has been a surge in internet use, both during and after the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who actively delay or evade responses to stress may merely offer momentary diversion from the stress but do not provide long-term relief. 7,18 It was also noted that such an avoidant coping style affected individuals' psychological distress more than an active coping style during the lockdown period. 18,19 A study revealed that a positive attitude and trust in God were the most used adaptive coping strategies during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to needing effective methods to prevent and treat COVID-19, the pandemic has brought unprecedented stress to individuals in the U.S. and throughout the world. Stressors related to the pandemic include direct effects of the virus, such as being diagnosed with and treated for the disease; and indirect effects such as job loss or income disruptions, closures of schools and agencies that provide essential care and support to families, and social isolation, interpersonal conflict, and loneliness as a result of complying with social distancing guidelines (e.g., Ahuja, 2021;Kujawa et al, 2020;Taylor et al, 2020). These COVID-19-related stressors place individuals at risk for symptoms of depression, anxiety, and other psychiatric disorders.…”
mentioning
confidence: 99%
“…Psychometric information most often concerned internal consistency assessed with Cronbach's α [e.g., 22]. Two studies performed an EFA [26,31], but no CFA has been conducted on any of the identi ed measures to con rm the dimensional structure. Overall, no measure has been psychometrically evaluated in more than one study.…”
Section: Introductionmentioning
confidence: 99%